2018
DOI: 10.1016/j.ijpsycho.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal brain dynamics underlying attentional bias modifications

Abstract: Exaggerated attentional biases toward specific elements of the environment contribute to the maintenance of several psychiatric conditions, such as biases to threatening faces in social anxiety. Although recent literature indicates that attentional bias modification may constitute an effective approach for psychiatric remediation, the underlying neurophysiological mechanisms remain unclear. We addressed this question by recording EEG in 24 healthy participants performing a modified dot-probe task in which pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 91 publications
2
6
0
Order By: Relevance
“…Regarding the interaction between IC training and attention, while negative results should be interpreted with caution, the absence of effect of the training on attentional biases to the trained NoGo stimuli speaks against an explanation of changes in stimulus valuation in terms of attentional modulations (Houben and Jansen, 2011;Veling and Aarts, 2011;Veling et al, 2013;Wessel et al, 2014;Houben and Jansen, 2015;Wessel et al, 2015). This finding is also in line with previous observation for an absence of interaction between changes in executive control performance and in automatic attentional allocation systems (Sallard et al, 2018). Interactions between inhibitory control and attentional biases might however manifest only during real food choices or consumption, and/or in case of extreme biases or abnormally weak IC (Dawe et al, 2004;Kakoschke et al, 2015).…”
Section: Nogo Stimuli's Reward Value Influences Training Induced Imprsupporting
confidence: 87%
“…Regarding the interaction between IC training and attention, while negative results should be interpreted with caution, the absence of effect of the training on attentional biases to the trained NoGo stimuli speaks against an explanation of changes in stimulus valuation in terms of attentional modulations (Houben and Jansen, 2011;Veling and Aarts, 2011;Veling et al, 2013;Wessel et al, 2014;Houben and Jansen, 2015;Wessel et al, 2015). This finding is also in line with previous observation for an absence of interaction between changes in executive control performance and in automatic attentional allocation systems (Sallard et al, 2018). Interactions between inhibitory control and attentional biases might however manifest only during real food choices or consumption, and/or in case of extreme biases or abnormally weak IC (Dawe et al, 2004;Kakoschke et al, 2015).…”
Section: Nogo Stimuli's Reward Value Influences Training Induced Imprsupporting
confidence: 87%
“…Specifically, attentional maintenance at the later stage of emotional stimuli processing did differ between clinical patients and healthy controls, whereas attentional orientation occurring at the early stage did not differ between the two groups. However, a systematic review article revealed that not only late ERP components including N2 (related to cognitive control: 250–300 ms) and P2 (related to emotional attention: 200–250 ms) but also early components including error‐related negativity (ERN, related to the error detection: roughly 50 ms post‐error commission) and P1 (related to the early visual processing: 100–130 ms), were affected by ABMTs 50–52 . It seems that ABMTs modulate both the early stage of attentional processing and the later processing associated with cognitive and emotional control.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies on the ERN represent the most comprehensive evidence on the generalizability of the beneficial effects of ABM beyond attention bias measures, other types of generalization have been assessed. In particular, in ABM protocols designed to develop attentional biases toward or away from colored shapes in college students, global ERPs | 9 of 16 CARLSON were assessed in a Go/Nogo task of inhibitory control and analyses revealed early (50-84 ms) amplitude differences between training conditions in occipitotemporal cortex (Sallard et al, 2018). Specifically, less activity was observed following ABM in an avoidance condition when attention was trained away from a particular stimulus.…”
Section: The Effects Of Abm On Far Transfermentioning
confidence: 99%
“…Specifically, it was found that ABM training away from threat (i.e., angry faces) resulted in reduced cue‐locked P1 amplitudes relative to ABM training towards threat (O'Toole & Dennis, 2012). Similarly, global ERP analyses revealed an early amplitude reduction in ABM protocols training attentional avoidance (Sallard et al., 2018). In addition, a study of pregnant women found that reduced cue‐locked P1 (and P2) amplitudes moderated the reduction of anxiety following ABM training away from threat (Dennis‐Tiwary et al., 2017).…”
Section: Effect Of Abm On Erpsmentioning
confidence: 99%